Answer:
hard, search on internet as I don't know this
Answer:
12
Step-by-step explanation:
f(x) = -x^3 + x^2
Let x = -2
Evaluate the expression
f(-2) = -(-2)^3 + (-2)^2
= - (-2)*(-2) * (-2) + ( -2) * (-2)
= -(-8) + ( 4)
= 8 + 4
= 12
Y=√(x+6) - 7
constraint: x+6> or = 0
or x> 0r = -6
RANGE = x∈R/ x > or = 0
<h3>part d is pair of adjacent angle is supplementary </h3>
- because the angle are complementary and common vertex so it is adjacent Two complementary angles with a common vertex and arm are called adjacent complementary angles
hope it's helpful thanks